Biomedical image acquisition system using a Gamma chamber - Jara, Abelardo (2003)
A gamma camera images PC acquisition board has been developed. The digital system has been described using VHDL and has been synthesized and implemented in aAltera Max7128S CPLD and two PALS 16L8. The use of programmable-logic technologies has afforded a higher scale integration and a reduction of the digital delays and also has allowed us to modify and bring up to date the entire digital design easily.